Metabolic Engineering of Lactobacillus plantarum for Direct l‐Lactic Acid Production From Raw Corn Starch. Issue 5 (22nd February 2018) - Okano, Kenji; Uematsu, Gentaro; Hama, Shinji; Tanaka, Tsutomu; Noda, Hideo; Kondo, Akihiko; Honda, Kohsuke
Abstract : Fermentative production of optically pure lactic acid (LA) has attracted great interest because of the increased demand for plant‐based plastics. For cost‐effective LA production, an engineered Lactobacillus plantarum NCIMB 8826 strain, which enables the production of optically purel ‐LA from raw starch, is constructed. The wild‐type strain produces a racemic mixture ofd ‐ andl ‐LA from pyruvate by the action of the respective lactate dehydrogenases (LDHs). Therefore, the gene encoding D‐LDH ( ldhD ) is deleted. Although no decrease ind ‐LA formation is observed in the Δ ldhD mutant, additional disruption of the operon encoding lactate racemase ( larA ‐ E ), which catalyzes the interconversion betweend ‐ andl ‐LA, completely abolishedd ‐LA production. From 100 g L −1 glucose, the Δ ldhD Δ larA‐E mutant produces 87.0 g L −1 ofl ‐LA with an optical purity of 99.4%. Subsequently, a plasmid is introduced into the Δ ldhD Δ larA‐E mutant for the secretion of α‐amylase from Streptococcus bovis 148. The resulting strain could produce 50.3 g L −1 ofl ‐LA from raw corn starch with a yield of 0.91 (g per g of consumed sugar) and an optical purity of 98.6%. The engineered L. plantarum strain would be useful in the production ofl ‐LA from starchy materials. Abstract : Fermentative production of optically pure lactic acid (LA) has attracted great interest because of the increased demand for plant‐based plastics. In this study, production of optically purel ‐LA is achieved by double‐knockout of the gene encoding D‐lactate dehydrogenase ( ldhD ) and the operon encoding lactate racemase ( larA‐E ) in Lactobacillus plantarum NCIMB 8826 strain. In addition, directl ‐LA production is achieved by introducing the plasmid for secretion of α‐amylase from Streptococcus bovis 148 to the Δ ldhD Δ larA‐E strain. The engineered L. pantarum strain would be applicable forl ‐LA production from starchy materials.